Analisis Penerapan Model Pembelajaran PjBL dan Konsentrasi Belajar Siswa Pada Materi Sistem Koordinasi di SMA Negeri 1 Pancur Batu: (Analysis of The Application of The PjBL Learning Model and Student Learning Concentration on Coordination System Material at SMA Negeri 1 Pancur Batu) - Winda R Aritonang, Frince; Ritonga , Ilham; Hasibuan , Rani (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2024)
Analysis of the implementation of the PjBL learning model and students' learning concentration on coordination system material at SMA Negeri 1 Pancur Batu. This research aims to analyze the application of the PjBL learning model and students' learning concentration in understanding the Coordination system learning at SMA Negeri 1 Pancur Batu. This type of research is qualitative research where an educator will be a resource person in obtaining information. Data collection was carried out by observation and interviews. This research was conducted on Saturday, March 23 2024. The sample used was one of the biology subject educators and one of the class XI students. From the results of observations and interviews with researchers, we found the following things: there are problems with students' ability to concentrate on learning during the teaching and learning process in the classroom. The learning model used does not actively involve students and teaching staff still implement teacher-centered learning. Educators use learning models that are still standard, namely lecture and discussion methods to explain the material. One of the teacher competitions to solve this problem is by using the Project Based Learning (PjBL) Learning Model. Abstrak. Analisis penerapan model pembelajaran PjBL dan konsentrasi belajar peserta didik pada materi sistem koordinasi di SMA Negeri1 Pancur Batu. Penelitian ini bertujuan untuk menganalisis penerapan model pembelajaran PjBL dan konsentrasi belajar peserta didik dalam memahami pembelajaran sistem Koordinasi di SMA Negeri 1 Pancur Batu. Jenis penelitian ini adalah penelitian kualitatif bahwa seorang pendidik akan menjadi narasumber dalam memperoleh informasi. Pengumpulan data dilakukan dengan observasi dan wawancara. Penelitian Ini telah dilakukan pada hari sabtu, 23 Maret 2024. Sampel yang dipakai adalah salah satu seorang tenaga pendidik mata pelajaran biologi dan salah satu ruang siswa kelas XI. Dari hasil observasi dan wawancara peneliti, kami menemukan hal-hal sebagai berikut terdapat permasalahan pada kemampuan konsentrasi belajar siswa pada saat proses belajar mengajar di ruang kelas. Model pembelajaran yang dipakai tidak melibatkan peserta didik secara aktif dan tenaga pendidik masih menerapkan pembelajaran yang berpusat pada guru. Tenaga pendidik menggunakan model pembelajaran yang masih standar yaitu metode ceramah dan diskusi untuk menjelaskan materi. Salah satu kompetisi guru untuk menyelesaikan permasalahan tersebut adalah dengan memakai Model Pembelajaran Project Based Learning (PjBL).